Leisure Satisfaction, Personality, and Psychosexual Adjustment Among College Students: A Latent Profile Analysis - Xia, Ximei; Wang, Xiaotian; Wang, Yuting (Frontiers in Psychology, 2022)
Although previous studies have explored the factors influencing sexual health, the impact of leisure, personality, and the interaction of those two factors on psychosexual adjustment remains unclear. This study investigated the relationship between leisure satisfaction and psychosexual adjustment based on the compensation theory and the social learning theory. In addition, we explored the personality antecedents and interaction between personality and leisure satisfaction on the basis of the personal-environment fit models. The participants in this study were 1161 college students. The results showed that there was a significant positive correlation between leisure satisfaction and psychosexual adjustment. Moreover, the four personality types (the overcontrolled, high-moderate, low-moderate and resilient groups) had different performance in psychosexual adjustment. Among them, the resilient group had the highest scores, while the overcontrolled group had the lowest scores. The results suggested that there was an interaction between personality and leisure satisfaction as well. Our research could enrich the research content of leisure and personality and could provide a practical basis for improving undergraduates’ psychosexual adjustment.